The Book of Job and the Fear of God - Wilson, Lindsay (Tyndale bulletin, 1995)
This article studies the function of the ‘fear of God’ idea in the book of Job. It is argued that, despite the difference in terminology, the ‘fear of God’ is equivalent to the ‘fear of the LORD’ concept of Proverbs. The location of the motif in the final form of the book of Job suggests that the ‘fear of God’ is not being proposed as the answer to Job’s dilemma. Rather, Job is one who maintains his ‘fear of God’ throughout the book, yet is left with his questions and suffering. The ‘fear of God’ is seen as the solution by Job’s friends, the wisdom interlude of chapter 28, and by Elihu, yet all this is overridden by the Yahweh speeches and epilogue, where the ‘fear of God’ is not mentioned. While the ‘fear of God’ is central to the wisdom stream, the book of Job establishes that it is not the answer to every problem in life.